Apps for developing pronunciation in English as an L2 - Baldissera, Luana Garbin; Tumolo, Celso Henrique Soufen (Revista X, 2021)
The goal of pronunciation teaching should be to enable learners to develop intelligible pronunciation and, in order to do this, it is important to teach perception and production of the most relevant segmental and suprasegmental features of pronunciation, considering specific groups of learners (CELCE-MURCIA et al., 2010). Technology has played an important role in pronunciation teaching, and the applications developed for pronunciation instruction enable learners not only to engage in pronunciation activities, but to have access to a greater variety of input and immediate feedback. Having this in mind, this study aimed at analyzing the content, the pronunciation teaching steps, the features, and usability resources of pronunciation apps. In order to guide the analysis, a framework was developed based on literature related to the areas of pronunciation teaching and of Mobile Assisted Language Learning (MALL). The results showed that there is a tendency for the apps analyzed to focus more on segmentals. All of them offer description and analysis, listening discrimination, and controlled practice of the pronunciation features, as well as feedback. However, they were limited in terms of guided and communicative practice, of Automated Speech Recognition (ASR), and of variety of input.